Synthesis method and application of polysulfone microcapsules for adsorbing indium - WANG SHIWEI; XIE CONGZHEN; HAN XIAOCHUN; WANG GENSHUI; LIU SHAOHUA; YANG ZHIFENG (2016)
The invention discloses a synthesis method and application of polysulfone microcapsules for adsorbing indium. Polysulfone serves as the raw material, the microencapsulation technology and the extraction technology are combined, an extraction agent is coated through the microencapsulation method, the optimum stirring and emulsifying speed, the optimum dispersing agent concentration, the optimum oil phase composition and the optimum water-oil ratio in the synthesis and extraction process are proposed according to the application of adsorbed indium, the problems of emulsification and phase separation are effectively avoided, and the surfaces of the prepared polysulfone microcapsules are smooth and compact; the preparation method is simple, equipment is simple and low in cost, and the solvent loss is small; an excellent adsorbing effect is achieved by applying the polysulfone microcapsules in adsorbing indium. 本发明公开了种吸附铟的聚砜微胶囊的合成方法和应用，以聚砜为原料，将微胶囊技术与萃取技术相结合，利用微囊化方法将萃取剂包覆起来，针对其吸附铟的用途，提出了合成萃取过程中最佳的搅拌乳化速度、分散剂的浓度、油相的组